Frogs : a day in the life : what do frogs, toads, and tadpoles get up to all day? - Caviedes-Solis, Itzue Wendolin; Rancourt, Henry (New York, NY : Neon Squid, 2023)
"A gripping story set over 24 hours where readers will come face-to-face with the most amazing frogs and toads in the world, written by expert Dr. Itzue W. Caviedes-Solis"--
Includes index.
Keywords: Frogs -- Juvenile literature